Stress Resilience is Associated with Hippocampal Synaptoprotection in the Female Rat Learned Helplessness Paradigm. (1st April 2021) - Huzian, Orsolya; Baka, Judith; Csakvari, Eszter; Dobos, Nikoletta; Leranth, Csaba; Siklos, Laszlo; Duman, Ronald S.; Farkas, Tamas; Hajszan, Tibor
Highlights: Helpless behavior of female rats is associated with the loss of hippocampal spine synapses. Diazepam strongly prevents the development of helpless behavior and averts the loss of hippocampal spine synapses. Almost all responses to fluoxetine are abolished following exposure to inescapable stress. Only high-dose fluoxetine is capable of reproducing the strong protective actions of diazepam. These protective actions are associated with muted corticosterone release during escape testing. Abstract: The synaptogenic hypothesis of major depressive disorder implies that preventing the onset of depressive-like behavior also prevents the loss of hippocampal spine synapses. By applying the psychoactive drugs, diazepam and fluoxetine, we investigated whether blocking the development of helpless behavior by promoting stress resilience in the rat learned helplessness paradigm is associated with a synaptoprotective action in the hippocampus. Adult ovariectomized and intact female Sprague-Dawley rats ( n = 297) were treated with either diazepam, fluoxetine, or vehicle, exposed to inescapable footshocks or sham stress, and tested in an active escape task to assess helpless behavior. Escape-evoked corticosterone secretion, as well as remodeling of hippocampal spine synapses at a timepoint representing the onset of escape testing were also analyzed. In ovariectomized females, treatment with diazepam prior to stress exposure prevented helpless behavior, blocked the loss of hippocampal spine synapses, and muted the corticosterone surge evoked by escape testing. Although fluoxetine stimulated escape performance and hippocampal synaptogenesis under non-stressed conditions, almost all responses to fluoxetine were abolished following exposure to inescapable stress. Only a much higher dose of fluoxetine was capable of partly reproducing the strong protective actions of diazepam. Importantly, these protective actions were retained in the presence of ovarian hormones. Our findings indicate that stress resilience is associated with the preservation of spine synapses in the hippocampus, raising the possibility that, besides synaptogenesis, hippocampal synaptoprotection is also implicated in antidepressant therapy.